Impact of glucose and high affinity glucose sensor on physiological responses in Candida glabrata - Ng, Tzu Shan (2016)
Emerging fungal pathogen, Candida glabrata displays its metabolic flexibility by colonizing several site of host niches with different nutrient availability. Glucose sensing and utilization could be particularly important for the regulation of C. glabrata metabolic adaptation. Further exploration on the central metabolism pathway could help in advancing the knowledge on the novel antifungal development and overcome the limited choice of antifungal available currently. In line with this objective, the present study embarked on a several efforts in deciphering the role of glucose and glucose sensing in the viability and fitness of C. glabrata. The first part of this research outlined the putative genes of C. glabrata that are involved in the glucose inducing-Sugar Receptor-Repressor (SRR) pathway by comparing its orthologs found in Saccharomyces cerevisiae. Expression of selected key genes was also studied to confirm their response in five different glucose concentrations. For the second part, the phenotypic and physiological response of three strains of C. glabrata namely, ATCC2001 (laboratory isolate), Cg 2737 (clinical blood isolate) and Cg 91152 (clinical vaginal isolates), towards various glucose concentrations were studied. These strains were examined under different glucose concentration for their ability to grow, form biofilm, resistance toward amphotericin B (antifungal drug) and hydrogen peroxide (oxidative agent). Clinical isolates of C. glabrata were found with the ability to grow in low glucose environment (0.01%) where ATCC2001 strain has failed to survive. Generally, ATCC2001 and Cg 2737 was found to be active in biofilm formation under lower glucose environment (0.01, 0.1% and 0.2%) in comparison to glucose-rich environment (1% and 2%). Besides, low glucose surrounding (0.01, 0.1% and 0.2%) was also found to promote the survivability of C. glabrata towards amphotericin B (1 μg/ml), while higher glucose environment (0.2%, 1% and 2%) promotes C. glabrata resistance towards hydrogen peroxide. It is speculated that nutrient crisis in lower glucose setting is supposed to direct C. glabrata to a less active life cycle and therefore led it to group and form biofilm for nutrient sharing purposes. Lower metabolic rate and lower flux rate of molecules within C. glabrata biofilm may also result in the incompetence of amphotericin B. Nevertheless, the promotion of anti H2O2 capability in C. glabrata by glucose requires further investigation. These observations have demonstrated the fine tuning of C. glabrata physiological behavior towards surrounding glucose levels as low as 0.01%. Besides, the higher expression of high affinity glucose sensor (SNF3) explained the ability of clinical isolates to grow in low glucose environment, in comparison to ATCC2001 strain. For the third part of this study, a SNF3 knockout strain was constructed to study the role of this gene in the physiology of C. glabrata, particularly its involvement in the glucose sensing pathway. The snf3Δ showed a weaker growth of mutant strain under lower glucose environment (0.01% and 0.1%) in comparison to wild type. However, no different in growth was found when they were subjected to higher glucose concentration surrounding (1% and 2%). In addition, deletion of SNF3 did not affect the ability of C. glabrata to form biofilm but instead disrupt the ability of C. glabrata to resist amphotericin B and survive in macrophage. Notably, deletion of SNF3 resulted in the changes of transcription level for several key genes in the SRR pathway and suggested the shutting down of glucose uptake pathway that under low glucose environment. The disruption of SNF3 was found to rattle the fitness of C. glabrata, particular in low glucose concentration environment, which is crucial for it to thrive in human niches site. This study has highlighted the impact of glucose on the physiology of C. glabrata and further decodes the involvement of SNF3 in mediating the glucose uptake, which contributes to the vitality of C. glabrata.